Carbon analysis from sediment core POS514_40-11 - Ivan Razum; Ozren Hasan; Slobodan Miko; Brunović Dea; Nikolina Ilijanić (PANGAEA, 2024)
In order to study influence of changing oceanographic setting and climate on carbon burial efficiency and provenance of detrital component a sedimentary core (POS514-40-11GC) was retrived from Mid Adriatic Deep (MAD), Adriatic Sea (Latitude: 43.483333, Longitude:15.433333 , water depth of 217 m) from R/V Poseidon during the cruise named "Micropaleontology, Actuopaleontology and Environmental Baseline Study of the Holocene to latest Pleistocene in the Northern and Eastern Adriatic Sea Basin" in May/June 2017. Content of total organic and inorganic carbon, nitrogen, stable carbon (δ13C extperthousand) and nitrogen isotopes (δ15N extperthousand), including dry density were analyzed down to the 623 cm in average resolution of six cm.